ESSENTIAL ELEMENTS OF CHILDREN’S STORY BOOKS IN ISLAMIC PEDAGOGY BASED ON AL-QURAN TO CULTIVATE PROSOCIAL BEHAVIOUR AMONG PRESCHOOL CHILDREN - Ilyani Mohd Rosmadi; Zainiah Mohamed Isa, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
It is a very concerning situation we are having today when seeing youngsters showing less involvement and not being helpful toward the ones in need. Having children to be exposed to storybooks is to introduce them with moral values that help in building their characters. Storybooks are developed containing pedagogies adapted from the Quran that convey the value of prosocial behaviour effectively. The pedagogies are narrative, dialogue, repetition and questioning. Typography, illustrations and simplified phrases are additional elements that are also included. This research involved 60 children aged 5 to 6 years old from selected preschools in Malaysia. 30 children are presented with the original version of the storybooks and the rest are presented with modified storybooks. Modified Prosocial Behaviour Questionnaire which consists of 15 items is required to be filled during pre and post-test. There was no significant difference on the pretest (M= 32.07, SD= 3.89) and post-test (M= 32.80, SD= 8.57) when using the original books; t(29)= -0.427, p= 0.672 while there was a significant difference on the pretest (M= 23.83, SD= 7.33) and post-test (M- 32.50, SD= 7.93) when using the modified books; t(29)= -16.478, p= 0.000.